Tindak Pidana Kekerasan Terhadap Anak Didik Dalam Dunia Pendidikan - Muhammad Rosikhu (Fakultas Hukum Universitas Mataram, 2017)
Violence is an act causing physical and psychological disorders. Violence has formed a distinctive feature in criminal field study. In indonesia, if violence not appear in economic and political sectors, it will appear in education sector. In education field, violence not only happen among students but also among teachers, and school guards. Giving physical punishment by teachers often interpreted the same as the crime of violence doing by parents. The purpose of this research is that to analyze regulation of violence against students and to analyze the criminal law policy on protection of teacher profession. This research is a normative law research conducted by collecting and reviewing the theory. Then, it is analyzed by analytical description method, and deductive deductions method. The result of the research concludes that the criminal law policy to overcome the crime of violence against children in education is limited in KUHP and law number 35 year 2014 on child protection. The use of physical punishment in schools by teachers has two juridical implications. First, teachers cannot be justified on the basis of material justification which is Tuchrecht. Second, it can still be accounted for based on the principle of loss and benefit. Protection of the teacher’s profession is regulated in law number 14 of 2005 on teachers and lecturers.